A qualitative evaluation of bystander training: What works?. Issue 4 (19th July 2022) - Roberts, Nicola; Marsh, Heaven
Abstract: Research shows that bystander training has the potential to reduce violence and abuse. It is not clear how and why the training works. We evaluated bystander training to find out what works. We found that interactive techniques, such as group discussions, 'the video', and the use of real‐world examples were the best ways of delivering the training because they stood out and were remembered by participants. These findings add to the paucity of research on what works in bystander training, and in doing so, raises implications for the design and delivery of future training.